Incubation temperatures and sex-ratios in the Malaysian leatherback turtle Dermochelys coriacea - Chan, E.H.; Liew, H.C. (Elsevier Science, 1995)
Sex-ratio studies on the leatherback turtles of the Rantau Abang Turtle Sanctuary reveal that incubation of eggs in an open-air beach hatchery produced predominantly female hatchlings, while indoor incubation at average temperatures not exceeding 29·21°C and at 30·4°C produced 100% male and female hatchlings respectively. Production of 100% female hatchlings from the beach hatchery was maintained for nest sizes of 25, 50, 75 and 100 eggs. Sand temperatures at nest depth throughout the nesting beaches of the Sanctuary, as well as within the three beach hatcheries currently operational in the Sanctuary during the nesting season, exceeded values for production of 100% female hatchlings.